2016
DOI: 10.1063/1.4945581
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from optimized structure of carbon nanotube field emitter array

Abstract: The authors report a detail study on the emission properties of field emitter array (FEA) of micro-circular emitters of multiwall carbon nanotubes (CNTs). The FEAs were fabricated on patterned substrates prepared with an array of circular titanium (Ti) islands on titanium nitride coated tantalum substrates. CNTs were rooted into these Ti islands to prepare an array of circular emitters. The circular emitters were prepared in different diameters and pitches in order to optimize their structure for acquiring a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Hence, changes in the cathode design, from the high aspect ratio lines to the matrix of squares have resulted in more uniform and 1.4 times higher emission current, probably due to the non-uniform distribution of CNT tips from the surface of the film. Further experiments by following researchers [118,119] showed an increase of emission currents with the reduction of the emitter area and the spacing between them (Figure 9a,b). All the results indicated the potential of a microscale design and the importance of the fine patterning for CNT-FE cathodes.…”
Section: Screen-printed Cnt-fe Cathodesmentioning
confidence: 90%
See 2 more Smart Citations
“…Hence, changes in the cathode design, from the high aspect ratio lines to the matrix of squares have resulted in more uniform and 1.4 times higher emission current, probably due to the non-uniform distribution of CNT tips from the surface of the film. Further experiments by following researchers [118,119] showed an increase of emission currents with the reduction of the emitter area and the spacing between them (Figure 9a,b). All the results indicated the potential of a microscale design and the importance of the fine patterning for CNT-FE cathodes.…”
Section: Screen-printed Cnt-fe Cathodesmentioning
confidence: 90%
“…However, it is difficult to discuss the effect of the treatment on emission due to a lack of data provided for comparison or other aspects influencing FE cathode properties, e.g., technology. Other methods were also investigated, such as the use of liquid elastomer [140], a soft rubber-roller [122,123,[141][142][143], mechanical crush [144], and plasma [119,133,[145][146][147]. The last one is believed not only to make CNTs protrude from the matrix (Figure 14c), but also to clear the cathode surface, improving the uniformity and reducing the cathode aging, and thus improving the FE characteristics (Figure 14d).…”
Section: Postprocess Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the operating voltage can be reduced by shortening the distance between the grid and the emitter, which beneficially reduces the likelihood of vacuum gap breakdown. To further study the effects of increasing the emission current, array arrangements of CNT film emitters were explored following on from reported dramatic improvements in emission characteristic by Li et al [37] and Chouhan et al [38]. A five-sheet-beam electron optical system based on the CNT film emitter was proposed, as shown in Figure 3.…”
Section: Sheet-beam Electron Optical System Based On the Carbon Nanotmentioning
confidence: 99%
“…The distance between two parallel CNT film emitters was G. In order to reduce the probability of breakdown, and at the same time to obtain a larger emission current density, the distance between the grid and the CNT film emitters was minimized to 1.5 mm. According to previous experiments [32], we have found that significant To further study the effects of increasing the emission current, array arrangements of CNT film emitters were explored following on from reported dramatic improvements in emission characteristic by Li et al [37] and Chouhan et al [38]. A five-sheet-beam electron optical system based on the CNT film emitter was proposed, as shown in Figure 3.…”
Section: Sheet-beam Electron Optical System Based On the Carbon Nanotmentioning
confidence: 99%